2015
DOI: 10.1590/s0036-46652015000300010
|View full text |Cite
|
Sign up to set email alerts
|

Head Lice in Hair Samples From Youths, Adults and the Elderly in Manaus, Amazonas State, Brazil

Abstract: A study of head lice infestations among young people, adults and elderly individuals was conducted from August 2010 to July 2013 in Manaus, AM, Northern Brazil. Hair samples collected from 1,860 individuals in 18 barber shops and beauty parlors were examined for the ectoparasite. The occurrence of pediculosis and its association with factors, such as sex, age, ethnicity, hair characteristics and the socioeconomic profile of salon customers, salon location and seasonal variation were determined. The overall occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…10 The present study examined a total of 66 410 patients suspected with head lice, of whom 2,547 cases (3.83%) were reported with confirmed infections consisting of 2395 female (94.03%) and 152 male (5.97%) cases. The prevalence of infection with this parasite was reported to be 11.14%, 65.7%, 2.84%, 16.3%, 72.2%, and 1.12% in epidemiological studies about the head lice infection (Pediculus humanus capitis) in different countries such as Turkey (in primary school girls), 14 Ethiopia (in children aged 9-11 years), 15 Brazil (in children and the elderly), 16 Poland (in youth), 17 Mexico (in children aged 10-13 years), 18 and Iraqi Kurdistan (in children 1-5 years), 19 respectively. Studies conducted in different parts of Iran have differently reported the overall prevalence of the head lice infection in different groups of society.…”
Section: Discussionmentioning
confidence: 99%
“…10 The present study examined a total of 66 410 patients suspected with head lice, of whom 2,547 cases (3.83%) were reported with confirmed infections consisting of 2395 female (94.03%) and 152 male (5.97%) cases. The prevalence of infection with this parasite was reported to be 11.14%, 65.7%, 2.84%, 16.3%, 72.2%, and 1.12% in epidemiological studies about the head lice infection (Pediculus humanus capitis) in different countries such as Turkey (in primary school girls), 14 Ethiopia (in children aged 9-11 years), 15 Brazil (in children and the elderly), 16 Poland (in youth), 17 Mexico (in children aged 10-13 years), 18 and Iraqi Kurdistan (in children 1-5 years), 19 respectively. Studies conducted in different parts of Iran have differently reported the overall prevalence of the head lice infection in different groups of society.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies conducted in different regions show contrasting results. While in the city of Manaus (Amazonas state) 24 , there was an occurrence of lice infestation in 3.68% in children, it could be noted that in Jundiaí (São Paulo state) 25 , and Nova Iguaçu (Rio de Janeiro state) 26 the prevalence of P. capitis was higher than 35%. It should be noted that most studies underestimate the general prevalence, assessing it over a specific period 27 .…”
Section: Introductionmentioning
confidence: 94%
“…Children aged 6-12 tend to gather in big groups are unaware of transmission mechanism [13]. After children, the elderly were the most affected [14]. They spend more time with children, attend nursing homes or similar collective environments.…”
Section: Questionnaire Analysismentioning
confidence: 99%